Development of an E-Learning Module to Enhance Students’ Critical Thinking Skills in Indonesian Language Learning - Wieke, Erzy Asty; Yuriska; Agung Setiawan; Sri Wahyudi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
To enhance students' critical thinking skills in learning the Indonesian language, this study developed an e-learning module based on the ADDIE model. Utilizing Google Classroom, the program was made interactive through discussion boards, HOTS (Higher Order Thinking Skills) exercises, and digital resources. The results showed a significant increase in debate participation (from 30% to 75%) as well as improvements in analytical (from 65% to 88%), evaluative (from 50% to 82%), and argumentative (from 55% to 80%) skills. These findings align with constructivist theory, which views technology as a catalyst for active learning. With the provision of infrastructure and training, limitations such as teacher readiness and access to technology can be addressed. The study recommends developing similar modules for other subjects, incorporating advanced elements such as gamification.